2021
DOI: 10.3389/fbioe.2021.630568
|View full text |Cite
|
Sign up to set email alerts
|

Flow Dynamics and Mixing in Extracorporeal Support: A Study of the Return Cannula

Abstract: Cannulation strategies in medical treatment such as in extracorporeal life support along with the associated cannula position, orientation and design, affects the mixing and the mechanical shear stress appearing in the flow field. This in turn influences platelet activation state and blood cell destruction. In this study, a co-flowing confined jet similar to a return cannula flow configuration found in extracorporeal membrane oxygenation was investigated experimentally. Cannula diameters, flow rate ratios betw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 52 publications
3
11
0
Order By: Relevance
“…Two circuits were used: one to drive the vessel flow in the vessel and another for the drainage by the cannula using a centrifugal blood pump. The setup was similar to that used by Lemétayer et al 19 The velocity field measurements were acquired using Particle Image Velocimetry (PIV). Zirconium dioxide particles with a diameter of 5 μm were used as tracers and the system comprised a high‐speed Nd:YAG laser (LPY703 50‐200, Litron Laser, Rugby, England) and a Dantec highspeed double frame CCD camera (Speedsense M120, Dantec Dynamics, Skovlunde, Denmark) with a 105 mm Nikkor lens (Nikkor, Nikkon, Tokyo, Japan).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Two circuits were used: one to drive the vessel flow in the vessel and another for the drainage by the cannula using a centrifugal blood pump. The setup was similar to that used by Lemétayer et al 19 The velocity field measurements were acquired using Particle Image Velocimetry (PIV). Zirconium dioxide particles with a diameter of 5 μm were used as tracers and the system comprised a high‐speed Nd:YAG laser (LPY703 50‐200, Litron Laser, Rugby, England) and a Dantec highspeed double frame CCD camera (Speedsense M120, Dantec Dynamics, Skovlunde, Denmark) with a 105 mm Nikkor lens (Nikkor, Nikkon, Tokyo, Japan).…”
Section: Methodsmentioning
confidence: 99%
“…In particular, the return cannula produces a flow field that resembles a confined jet where the ratio of vessel to cannula diameter sets the level of confinement. Although confined jets from an engineering perspective are well studied, few fluid‐dynamical studies addressed geometries as confined as found in ECMO cannulation 19 . Regarding the drainage cannula, the flow is characterized by strong shear layers developing in the suction region.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In 2018, Togo et al ( 23 ) showed comparable results in an experimental setting in four goats; in their study, the tip-to-tip distance in femoro-jugular configuration was associated with the R f as assessed with the limited oxygen saturation calculation method. In an experimental model it was recently shown that a distance of nine to twelve cannula diameters was required for the mix of native venous and ECMO blood to become homogenous ( 24 ). Further investigation is necessary with respect to the association of higher Rf with lower heart rate.…”
Section: Discussionmentioning
confidence: 99%
“…This interplay between pulsatile cardiac and steady-state ECMO flow results in regions involving high shear flows, abnormal pulsatility, and differential perfusion pressures. 14 A thorough understanding of both global and regional blood pressure and flow phenomena in different cannulation configurations will aid in patient-specific decision making in ECMO management.…”
Section: Calibration We Augmented the 3d Geometrical Model To Represe...mentioning
confidence: 99%